Quantifying Fermentable Sugars in Beer: Development and Validation of a Reliable HPLC-ELSD Method - Pedro F. Lopes; Fábio T. Oliveira; Luis F. Guido (Applied Sciences, 2025)
A high-performance liquid chromatography with evaporative light scattering detection (HPLC-ELSD) method was developed and validated for analyzing fermentable and reducing sugars in brewing matrices. The method exhibited detection limits of 2.5–12.5 mg/L and quantification limits of 12.0–30.0 mg/L. Linearity was achieved for all sugars, fitted with a quadratic calibration model (R2 = 0.9998). Precision metrics revealed relative standard deviations (RSDs) below 2% for repeatability and below 6% for intermediate precision. Recovery rates between 86 and 119% confirmed robustness and minimal matrix interference. Application to brewing samples highlighted variability in sugar profiles, with sucrose concentrations in wort ranging from 3.5 to 22.0 g/L and maltose and maltotriose in finished beers between 0.80 and 1.50 g/L and 1.10–2.50 g/L, respectively. Batch variability analysis showed that brewing conditions had a greater impact on sugar concentrations than malt batch origin, with maltose variation reaching 34.6%. This HPLC-ELSD method provides a robust and reliable tool for sugar analysis in brewing, offering valuable insights into fermentation dynamics and batch consistency. Its application to industrial contexts underscores its potential for improving quality control and optimizing brewing processes.